The Welleye: A Conceptual Framework for Understanding and Promoting Wellbeing - Dolan, Paul; Laffan, Kate; Kudrna, Laura (Frontiers in Psychology, 2021)
We present the Welleye – a novel and conceptually clear framework that links the objective circumstances of people’s lives and selves to what they attend to and how they feel day to day. We argue that these factors dynamically interact with one another to promote or impede people’s experiential subjective wellbeing with attention playing a central role in determining how people’s circumstances, selves, and the attentional stimuli that they are exposed throughout their daily lives feed into how people feel. Policymakers and organisations can use the framework to better understand how people are faring and design and evaluate interventions aimed at making people better off.